Advertising campaing planning: developing an advertising based marketing plan - Avery, Jim (Chicago, 2000)
Sus temas principales Target audience, working procedures,writing style, computer considerations, campaing outline,situation analysis
Incluye bibliografía
Keywords: Publicidad Multimedia